The effectiveness of the Islamic Education Curriculum in shaping the morals of students in Generation Alpha - Indah Salwa; Nada Lutfiyah Eka Putri; M. Fathoni Ladako (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Islamic Religious Education (PAI) curriculum has a strategic role in shaping students' morals. However, its effectiveness is still debatable due to various factors, such as teaching methods, teacher involvement, and learners' social environment. This study aims to examine the extent to which the Islamic Education curriculum contributes to shaping students' morals as well as identifying its supporting and inhibiting factors. Using a qualitative approach, this study involved in-depth interviews, observations, and analysis of relevant documents. The results showed that the effectiveness of the PAI curriculum is highly dependent on the implementation by educators, the relevance of the material to the reality of students' lives, as well as support from the family and community environment. It was found that students who received applicable and exemplary-based PAI learning were more likely to show good moral. However, there are obstacles such as the lack of innovation in learning methods and the lack of integration of Islamic values in daily life. Therefore, improvements in curriculum design, increased teacher competence, and a more contextual approach are needed so that the moral formation of students can run more effectively.